Carbon Accounting:: A Review of Disclosure Practices and Assurance Mechanisms - Hasan, Mahade; Mowla, Kazi Golam Rabbani (Jahangirnagar University Journal of Management Research, 2024)
This study aims to synthesize and critically evaluate the current state of carbon accounting research, focusing on its definition, disclosure practices, and assurance mechanisms. A systematic literature review analyses 125 articles published between 2000-2023 in ABDC A*, A, and B-ranked journals employing comprehensive keyword searches, inclusion criteria application, and manual screening for relevance. This review makes three key contributions to carbon accounting literature. First, we identify the persistence of definitional fragmentation despite calls for interdisciplinary approaches, revealing urgent need for standardized frameworks. Second, we reconcile contradictory findings on disclosure determinants by documenting that while firm size, governance quality, and industry carbon-intensity consistently drive disclosure practices, ownership structures, financial characteristics, and board committees remain inconclusive due to methodological inconsistencies. Third, we reveal significant gaps in carbon assurance research, particularly regarding quality measurement and methodology assessment. This study uniquely integrates definition, disclosure, and assurance research streams while systematically identifying measurement inconsistencies that explain contradictory prior findings. Future research should develop standardized disclosure quality frameworks, investigate moderating factors, expand geographical coverage, and explore carbon assurance quality standards.